Increased cell viability and proliferation in post-hypoxic hippocampal tissue culture treated with Acalypha indica root extract (Medical Journal of Indonesia, 2011)
Background: This research was done to study the influence of Acalypha indica Linn root extract towards relative cell viability and proliferation as parameters of neurogenesis in post-hypoxic hippocampal tissue culture. Methods: Experimental in vitro study using 24 primary neuronal cell cultures obtained from adult Sprague Dawley rat exposed to hypoxia with 5% O2/5% CO2/N2 balance gas for 24 hours. Post-hypoxia, Acalypha indica Linn root extract was added at doses of 10, 15, and 20 mg/mL to 3 treatment groups. No treatment was given to the control group. Each group consists of 6 samples. After 90 hours of incubation, relative cell viability was measured by using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) examination, and cell proliferation was measured byÂ using 5-bromo2-deoxy-uridine (BrdU) for cell proliferation. Data was analyzed using one way ANOVA parametric tests, then further analyzed with post-hoc analysis. Results: The relative cell viability of rat hippocampal tissue culture treated with Acalypha indica Linn root extract with dose of 10, 15, and 20 mg/mL was significantly higher than control (176.95%, 220.62%, and 386.02% vs. 100%). Cell proliferation of rat hippocampal tissue culture treated with Acalypha indica Linn root extract with dose of 10, 15, and 20 mg/mL was significantly higher than control (0.132, 0.117, 0.114 vs 0.096). Conclusion: Acalypha indica Linn root extract with doses of 10, 15, and 20 mg/mL can increase relative cell viability and proliferation in post-hypoxic hippocampal tissue culture. (Med J Indones 2011; 20:94-9)